Adaptive shift of active electroreception in weakly electric fish for troglobitic life - Soares, Daphne; Gallman, Kathryn; Bichuette, Maria Elina; Fortune, Eric S. (Frontiers in Ecology and Evolution, 2023)
The adaptive-shift hypothesis for the evolution of cave-dwelling species posits that ancestor species in surface habitats had exaptations for subterranean life that were exploited when individuals invaded caves. Weakly electric Gymnotiform fishes, nocturnal South American teleost fishes, have features that appear to be likely exaptations for troglobitic life. These fishes have active electrosensory systems in which fish generate weak electric fields that are detected by specialized electroreceptors. Gymnotiform fishes use their electric fields for navigation, prey capture (scene analysis), and social communication. Although active electrosensory systems appear to be exaptations for troglobitic life, as fish use these systems to ‘see in the dark’, producing these electric fields is energetically costly. Cave habitats, which often are low in resources, may not be able to support these high energetic demands. We showed that Eigenmannia vicentespelaea, a species of weakly electric fish that is endemic to the São Vicente II cave in central Brazil, surprisingly generate stronger electric fields than their surface relatives. The increase in strength of electric fields may result from differences in size between cave and surface populations, impacts of increased ‘sensory volumes’ and acuity, and lack of predation pressure in the cave. Eigenmannia vicentespelaea exhibits the classical phenotypes of any troglobitic fish: these fish have small to nonexistent eyes and loss of pigmentation. The closest living surface relative, Eigenmannia trilineata, inhabits streams nearby and has eyes and pigmentation. We examined the electrosensory and locomotor behavior of both species of fish in their natural habitats using a grid recording system. While surface Eigenmannia exhibits dramatic circadian changes in social behavior, such as hiding under rocks during the day and foraging in groups at night, ``cave Eigenmannia display territorial behavior with no apparent circadian modulations. This territorial behavior involves electrical and movement-based interactions that may be a form of boundary patrolling. Electrosocial behavior and scene analysis are mechanistically interlinked because both stem from active sensing tactics. Future studies will have to determine how selection on scene analysis will affect social behavior and vice versa.